Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to solve the following equation: $z^2 - (2 + 2i)z - 5 -10i = 0$?

My attempts so far has been trying to complete the square of $z^2 - (2 + 2i)z - 5 -10i$ but I have had no real progress with that. How would you approach this kind of problem?

Thank you very much for your help!

share|cite|improve this question
up vote 2 down vote accepted

Alternatively, by completing the square: $$\begin{aligned}z^2-(2+2i)z - 5 - 10i &= z^2-2(1+i)z - 5 - 10i\\&= z^2-2(1+i)z +(i+1)^2 -(i+1)^2 - 5 - 10i\\&= \left(z-(1+i)\right)^2 - (i+1)^2 - 5 - 10i\\&= (z-(1+i))^2 -5-12i\end{aligned}$$

share|cite|improve this answer

Hint: Try using the quadratic formula $$ z_{1,2}=\frac{-b\pm \sqrt{b^2-4c}}{2}=\frac{2+2i\pm \sqrt{(2+2i)^2+4(5+10i)}}{2}=\cdots $$

Edit: The quadratic formula comes from completing a square, here how it goes in this case: $$ z^2-2(1+i)z-5(1+2i)= (z-(1+i))^2 -(1+i)^2-5(1+2i)=0 $$ Moving the last two guys to the right gives that the solutions are $$ z_{1,2}-(1+i)=\pm \sqrt{(1+i)^2+5(1+2i)} $$ which is the same as the equation in the hint.

BTW: I do not do the actual calculations on purpose.

share|cite|improve this answer
If the quadratic formula works, you should be able to "complete the square" of $z^2 - (2 + 2i)z - 5 -10i$ as well? Thank you for your hint! – Lukas Arvidsson Feb 20 '13 at 9:28
Of course, the quadratic formula comes from completing a square! – Lior B-S Feb 20 '13 at 9:30
Yes that I what I thought as well @Lior B-S. But I seem to lack a strategy when trying to do complete the square of this equation – Lukas Arvidsson Feb 20 '13 at 9:34
Added it to the answer – Lior B-S Feb 20 '13 at 9:36
Thank you very much! – Lukas Arvidsson Feb 20 '13 at 9:36

The discriminant of the equation is $(2+2i)^2-4\cdot1\cdot\{-(5+10i)\}=20+8i=4(5+12i)$

Let $\sqrt{5+12i}=a+ib\implies(a+ib)^2=5+12i$

Equating the real & the imaginary parts, $a^2-b^2=5,2ab=12$ so, $(a^2+b^2)^2=(a^2-b^2)^2+(2ab)^2=13^2\implies a^2+b^2=13$

So, $a^2=9\implies a=\pm3,b=\pm2$

So, $\sqrt{5+12i}=\pm(3+2i)$

So, $z=\frac{2+2i\pm2(3+2i)}{2\cdot1}$

share|cite|improve this answer
@Lucas, I think the calculation of the square root of the discriminant (as it is of the form $a+ib$ ) is what makes it different from Quadratic Equation with real coefficients. – lab bhattacharjee Feb 20 '13 at 9:52

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.